An analysis of seasonality fluctuations in the oil and gas stock returns - Muhammad Surajo Sanusi; Farooq Ahmad (Cogent Economics & Finance, 2016)
This paper investigates the existence of seasonality anomalies in the stock returns of the oil and gas companies on the London Stock Exchange. It employs F-test, Kruskal-Wallis and Tukey tests to examine days-of-the-week effect. Generalised autoregressive conditional heteroscedasticity specification was also employed to investigate both the days-of-the-week and months-of-the-year effects. The analysis had been extended to some key FTSE indices. Our results showed no evidence of any regularity or seasonal fluctuation in the oil and gas stock returns despite the seasonal changes of demand in the companies' products. However, January effect has been observed in FTSE All Share and FTSE 100 indices.
Keywords: G1; 330; seasonality; oil and gas stock returns; days-of-the-week effect; months-of-theyear effect; January effect and London Stock Exchange